Prevalence and Etiology of Pediatric Maxillofacial Injuries - Samreena; Alam, Jehan; Shah, Ruqaya; Sheikh, Zulakha Akhtar; Naseem, Sobia; Ahmed, Javeria (Indus Journal of Bioscience Research, 2025)
Background: The prevalence of maxillofacial injuries in children is less than in adults; however, the presence of ongoing facial growth and development makes these injuries more challenging. Such injuries may have important physical or psychological effects, so prompt and adequate treatment is needed. to assess the frequency, causes, anatomical distribution, and treatment outcomes of maxillofacial injuries in children presenting to Jinnah Postgraduate Medical Centre (JPMC), Karachi. Methods: A descriptive cross-sectional study was conducted at JPMC for one year, from January 2023 to December 2023, in which 103 children between the ages of 1-15 years with diagnosed maxillofacial trauma were registered. Information regarding age, sex, cause of injury, site of involvement, treatment, and clinical outcome was gathered using structured proformas and clinical record forms. The relationships between gender and injury-related factors were assessed using Chi-square tests, with significance defined as p ≤ 0.05. Results: Most of the injuries sustained were in children between the ages of 6 and 10, with a slight male predominance. The predominant causes of trauma were falls and road traffic accidents. The facial bone that sustained the greatest injury was the mandible, followed by the zygomatic and maxillary bones. The bulk of the patients were treated conservatively, while a smaller subset required surgical intervention. Most patients recovered without complications; however, a small number suffered from infections or malunion. Conclusion: In children, particularly in boys, the leading causes of maxillofacial injuries are also associated with falls and road accidents. Familiarity with the prevailing trends of injury enables quick intervention and focused management, which are critical in effective treatment and prevention mechanisms. To alleviate the incidence of such problems, there is a need to focus on child care and education as well as traffic laws.